2016
DOI: 10.5114/kitp.2016.64886
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of myocardial bridge involving left anterior descending, obtuse marginal and ramus intermediate coronary arteries

Abstract: Myocardial bridging, a congenital coronary anomaly, is a cluster of myocardial fibers crossing over the epicardial coronary arteries. It is most frequently seen in the left anterior descending artery (LAD), and rarely involves the circumflex (CX) and right coronary artery (RCA). We report a patient with an unusual coronary bridge crossing over the left anterior descending, obtuse marginal and ramus intermediate branches. The patient presented with exercise-induced angina pectoris that was relieved with medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
1
3
0
1
Order By: Relevance
“…Kumar, et al [4] previously reported a case of myocardial bridging in 34-year-old Indian male, involving left main, LAD, left circumflex, and proximal major obtuse marginal branch. Kiris, et al [5] reported myocardial bridging involving the same combination as our patient, but in younger (46-year-old) Turkish male. This is the second reported case of myocardial bridging involving LAD, ramus intermedius, and OM1.…”
Section: Discussionsupporting
confidence: 78%
“…Kumar, et al [4] previously reported a case of myocardial bridging in 34-year-old Indian male, involving left main, LAD, left circumflex, and proximal major obtuse marginal branch. Kiris, et al [5] reported myocardial bridging involving the same combination as our patient, but in younger (46-year-old) Turkish male. This is the second reported case of myocardial bridging involving LAD, ramus intermedius, and OM1.…”
Section: Discussionsupporting
confidence: 78%
“…However, very few original papers mentioned MB of the LCX artery, but did not describe it in detail [20][21][22][23][24][25][26]. Furthermore, several researchers have reported case reports stating the characteristics of MB of the LCX artery [7][8][9][10][11][12][13][14]. Even though most MBs are considered congenital and asymptomatic, most cases have reported that patients with MB of the LCX artery experienced severe and chronic chest pain [7][8][9][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several researchers have reported case reports stating the characteristics of MB of the LCX artery [7][8][9][10][11][12][13][14]. Even though most MBs are considered congenital and asymptomatic, most cases have reported that patients with MB of the LCX artery experienced severe and chronic chest pain [7][8][9][11][12][13][14]. In 2005, Gunduz et al rst described a case of myocardial infarction in the rst OM of the LCX artery [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Вперше залягання епікардіальної вінцевої артерії в м'язовому сегменті описав Рейман у 1737 році, назвавши м'язовий сегмент місточком, а артерію, розташовану в його межах, тунельованою (пірнаючою). Частота виявлення цієї аномалії при патологоанатомічному дослідженні становить 7-85% випадків, що значно відрізняється від ангіографічних знахідок, які варіюють від 0,5 до 4,5% [1][2][3][4][5][6][7][8][9][10]. Ці факти свідчать про труднощі прижиттєвої діагностики ТКА, визначаючи актуальність вивчення і необхідність розробки алгоритмів діагностики та лікування хворих із цією аномалією.…”
unclassified